Molecular characterization of the rostral-most somites in early somitic stages of the chick embryo - Rodrigues, Sofia (2006)
Segmentation consists on the progressive formation of repetitive embryonic structures, named somites, which are formed from the most rostral part of the presomitic mesoderm. Somites are subdivided into anterior and posterior compartments and several genes are differentially expressed in either compartment. This has provided evidence for the importance of establishing the anterior–posterior polarity within each somite, which is critical for the correct segmented pattern of the adult vertebrate body. Although all somites appear morphologically similar, fate map studies have shown that the first 4 somites do not give rise to segmented structures, in contrast to more posterior ones. Moreover, in several somitogenesis-related mutants the anterior somites are not affected while posterior somites present clear defects or do not form at all. Altogether these data suggest relevant differences between rostral and caudal somites. In order to check for molecular differences between anterior and posterior somites, we have performed a detailed expression pattern analysis of several Notch signalling related genes. For the first time, we show that the somitic expression pattern profile is not the same along the anterior– posterior axis and that the differences are not observed always at the same somite level.